Field notes contributed by Dennis Thompson, summer 2000 - Thompson, Denniset al (2000)
Summer report of birds found in central Iowa contributed by Dennis Thompson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed